2021
DOI: 10.1177/21582440211006695
|View full text |Cite
|
Sign up to set email alerts
|

Key Success Factors (KSFs) Underlying the Adoption of Social Media Marketing Technology

Abstract: In developing world, most decisions by Micro, Small, and Medium Enterprises (MSMEs) to adopt social media marketing technology (SMMT) rely heavily on study findings from the Western World without much recourse to cross-context differences in structure and managerial capabilities. Thus, the lack of inquiries that provide complete guideline on the adoption of SMMT in developing economies hinders the development of integrated framework(s) that explains MSMEs’ successful adoption. The study used technology–organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 79 publications
3
57
0
1
Order By: Relevance
“…Therefore, social media is highly compatible with existing SMEs’ infrastructure as the technology is extremely simple and can be effortlessly adopted and used by any firm (Tajudeen et al, 2018). This result is in line with previous studies that have also confirmed the positive and significant association between these constructs (Ahani et al, 2017; Eze et al, 2021; Hamad et al, 2018).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, social media is highly compatible with existing SMEs’ infrastructure as the technology is extremely simple and can be effortlessly adopted and used by any firm (Tajudeen et al, 2018). This result is in line with previous studies that have also confirmed the positive and significant association between these constructs (Ahani et al, 2017; Eze et al, 2021; Hamad et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Coupled with COVID-19’s effects, continuing improvements in technology and increased globalization are forcing SMEs toward adopting social media in emerging countries. Therefore, in response to the dynamic business environment, increasing competition, and customer shifts in using online platforms, social media has been proposed as a significant influencing factor for increasing SMEs’ performance, thus supporting emerging economies (Alraja et al, 2020; Eze et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has provided the opportunity for two-way communication, become a part of everyday life, and reduced consumers’ anxiety around the globe (Alalwan et al, 2017; Dwivedia et al, 2021). It has gained wide popularity among advertising communities, and became one of the world-leading marketing platforms to share real-time business information (Coursaris et al, 2016; Eze et al, 2021; Vinerean et al, 2013; Yadav & Rahman, 2017). For instance, Facebook had 2.5 million advertisers, more than 50 million small businesses in 2016, and earned $ 5.4 billion in 2014 (Alalwan et al, 2017; Thornhill et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the growing scholarly prowess of T-O-E framework in the IS field and given that nothing remains same overtime, scholars [ 24 ] glamour for improving T-O-E’s lenses via context extension and theory integration. Eze et al, [ 53 ] berated [ 54 ] for proposing a specified model rather using the T-O-E taxonomy to categorize factors into relevant contexts. However because this paper is exploratory, the codes and themes in the analysis will provide us with typical extension(s) of the contexts in order to provide a more substantial analytical utility for micro-businesses.…”
Section: Introductionmentioning
confidence: 99%